Avaliação agronômica de genótipos de abacaxizeiros resistentes à fusariose no Estado do Espírito Santo - Altoé, Marcelo Soares (2020)
Tropical and subtropical America is considered the center of origin of the pineapple, with the Amazon Region being the largest center of diversity. This plant belongs to the Bromeliaceae family, genus Ananas and species Ananas comosus var. comosus. Nowadays, one of the great challenges in the production of pineapple is the study of new cultivars resistant to fusariosis and adapted to different producing regions. In addition, it is important to evaluate the sensory acceptance of new materials, since the launch of a fusarium-resistant cultivar alone does not meet the expectations of the fruit production chain. In this way, two chapters were developed analyzing the vegetative growth, the correlation between plant characters and productive aspects, physicochemical characteristics of the fruits and sensory analysis test of the fruits of four new pineapple hybrids, namely, BAG 344 x Perolera (04), BAG 344 x Soomth Cayenne (08), BAG 344 x Gold - (61), Perolera x Smooth Cayenne (73), genotype 344 and cv. Pearl. In the first chapter, the objective was to evaluate the relationship of leaf D with the physical characteristics of the fruits of four new fusarium-resistant pineapple hybrids, genotype 344 and cultivar Pérola, in the edaphoclimatic conditions of the southern state of Espirito Santo. Evaluations of the vegetative growth of the plants and xi their correlation with the fruits were carried out. The cv. Pérola showed greater vegetative growth. Hybrid 08 and cv. Pérola showed no significant correlation between the fresh weight of the fruits and the characters of the leaf D. In the second chapter, the objective was to evaluate new cultivars of pineapple for consumption in natura with superior organoleptic quality, desirable agronomic characteristics and resistant to fusariosis. Evaluations were carried out during the production cycle: plant development; physico-chemical characterization of fruits and sensory analysis of fruits. The studied hybrids showed resistance to fusariosis. Hybrid 08 stood out with desirable characteristics for the development of the plant. Hybrids 04 and 08 showed fruits with greater fresh weight, while genotype 344, fruits with less fresh weight. For chemical characteristics, hybrids 08 and 61 and cv. Pearl, with higher ratio value. For sensory analysis, cv. Pérola was superior to the other genotypes, showing greater acceptance. Hybrid 04 and genotype 344 showed greater potential for adaptation to growing conditions in the south of the State of Espirito Santo and to the final consumer. This study contributed to the recommendation of new hybrids with high productive potential and superior sensory quality, adapted to the main producing region of Espírito Santo